ANALYSIS OF WATER MANAGEMENT IN A COOPER-GOLD MINE DURING THE POST MINING PHASE WITH BIMODAL RAINFALL DISTRIBUTION - Zahy Ghazian Ihsan, Muhamad
The PT XYZ mine, which employs the open pit mining method for copper and gold extraction, is approaching the post-mining phase set to begin in 2033. During the post-mining phase, it is necessary to conduct an analysis and evaluation of the existing drainage system since it will no longer be usable as it was during the mining operations. The planned drainage system includes a base plan for pit backfilling, excluding the eastern forest area, using a bimodal rainfall distribution that affects runoff characteristics. This study aims to analyze the planned drainage system, analyze the catchment area in the post-mining phase, analyze runoff hydrographs based on bimodal rainfall patterns, and provide recommendations for the drainage system design. The methods used include processing rainfall data, analyzing runoff hydrographs, designing drainage facilities, analyzing the catchment area in the post-mining phase, and evaluating the design. The research results indicate that changes in the catchment area are required in several areas. Additionally, the runoff hydrograph with a bimodal rainfall pattern produces two peak runoff flows, with the highest flow rate being 150.6 m³/s in the Barakebo Forest open channel. Recommendations for the drainage system include designing and dimensioning open channels, drop structures, and culverts to optimize postmining water management.